Affordability Assessment of Industrial Product-Service System in the Aerospace Defence Industry - Bankole, O. O.; Roy, Rajkumar; Shehab, Essam; Wardle, P. (Cranfield University Press, 2009)
The Industrial Product-Service System (IPS2) takes a whole life cycle view in order to consider the total cost of the IPS2 offering. This paper focuses on the concept of customer affordability which aims to review current practice in industry and with interaction between customer and solution providers to identify factors affecting affordability. It secures a standard definition and proposes a measurement technique called the Affordability Index (AI) within the aerospace defence industry. A preliminary Affordability Capability Audit Tool is developed to give an indication of the confidence level about the AI. It identifies challenges in industry and outlines opportunities for further research scope.
Organised by: Cranfield University
Keywords: Product-Service System, Aerospace Defence Industry; Affordability Assessment; Affordability Index; Affordability Capability Tool